Ethnomedicinal uses of Boerhavia diffusa among indigenous communities in the Indian subcontinent - Pandey, Sandeep (Ethnobotany Research and Applications, 2025)
Background: Plants and their derivatives have been used to address various human health issues since ancient times. Indigenous communities are the main source of knowledge regarding these plants, and scientific validation is often required for their medicinal uses. Boerhavia diffusa L., commonly known as punarnava or spreading hogweed, is a valuable medicinal herb with numerous pharmacological advantages. Recognized in Ayurvedic medicine as a rejuvenator or "Rasayan," it is noted for its impressive anti-aging and antioxidant effects. The purpose of this study was to gather recent information on the ethnomedical uses of Boerhavia diffusa L. to explore diverse therapeutic applications and determine any potential pharmacological benefits. Methods: Relevant data on the ethnomedical uses of Boerhavia diffusa L. and its parts—root, leaf, stem, entire plant, flower, and seed—was gathered from books, articles, theses, and patents that were published in online databases like Google Scholar, PubMed, Science Direct, SciELO, and SpringerLink, among others. Ethnobotanical indices have been utilized to verify the authenticity of the gathered information. Results: The literature review reveals that boeravinone, a rotenoid found in the roots and leaves of the medicinal plant, is one of its active compounds. The plant contains a range of active substances, which include purine nucleosides, lignans, xanthones, alkaloids, flavonoids, phytosterols, and steroids. In the Indian subcontinent, indigenous communities and local healers utilize the plant and its components, primarily the roots, followed by the leaves and whole plant, to address jaundice, kidney issues, digestive disorders, heart problems, asthma, eye conditions, urinary issues, and anemia, in addition to forty-six other health concerns. Conclusion: The findings indicated that B. diffusa has various ethnobotanical uses within ethnic groups in the Indian subcontinent, highlighting the need for focused efforts to optimize its benefits and applications. To accurately identify the specific functions of its bioactive components for multiple pharmacological purposes, additional clinical trials and further research are necessary for its diverse therapeutic applications. Keywords: Boerhavia diffusa, Traditional medicine, Folklore uses, Indian sub-continent